ТЕРМІЧНА СТІЙКІСТЬ ВИСОКОВОЛЬТНОЇ КАБЕЛЬНОЇ ЛІНІЇ В АВАРІЙНИХ УМОВАХ ПЕРЕВАНТАЖЕННЯ І КОРОТКОГО ЗАМИКАННЯ - Щерба, А.А.; Подольцев, О.Д.; Кучерява, І.М.; Антонець, Т.Ю. (Інститут електродинаміки НАН України, Київ, 2026)
The paper proposes new knowledge in cable engineering by studying the operation of up-to-date high-voltage cable line under the non-nominal and emergency conditions to ensure its reliability and service life. The temperature conditions for operation of an underground 110 kV three-phase cable line with cross-linked polyethylene insulated cables in the nominal and emergency modes of short circuit and short-term overload of cables are studied by computer finite-element method. A number of practically important problems for designing such cable lines are solved. In particular, the computation of the three-phase short-circuit mode in the line is carried out taking into account its reconnection after short circuit with certain delay time (5, 10 or 15 s) and at different loads (50% and 100% of the nominal current). The results obtained allow determining the permissible operating time for the line operation with the temperature of the cable conductor not higher than the permissible limiting value. The nature of the increase in the temperature of the cables within the time of different current overloads varying from 120% to 200% is investigated. The results give a possibility to determine the permissible operating time of the line when the temperature of the cable conductor does not exceed 130°С. In the case of the double-circuit cable line, the computational results for non-stationary thermal process under emergency condition of one circuit failure and the transmission of double power through the other circuit are presented. It is shown that the limiting conductor temperature of 130°C is reached after 1.3 hours of line operation. The problems solved in the paper answer the questions regarding the thermal stability of the high-voltage cable line in emergency modes and are of interest to designers of such lines as well as organizations responsible for their safe operation and power companies for more efficient use of cable lines. References 36, figures 5, tables 2.